Hydrogen as Carbon Gasifying Agent During Glycerol Steam Reforming over Bimetallic Co-Ni Catalyst - Cheng, C. K.; Lim, Rwi Hau; Anabil, Ubil; Chin, S. Y.; Jolius, Gimbun (Scientific Research Publishing, 2012)
Alumina-supported bimetallic cobalt-nickel catalyst has been prepared and employed in a fixed-bed reactor for the direct production of synthesis gas from glycerol steam reforming. Physicochemical properties of the 5Co-10Ni/85Al2O3 catalyst were determined from N2-physisorption, H2-chemisorption, CO2 and NH3-temperature-programmed desorption measurements as well as X-ray diffraction analysis. Both weak and strong acid sites are present on the catalyst surface. The acidic:basic ratio is about 7. Carbon deposition was evident at 923 K; addition of H2 however has managed to reduce the carbon deposition. Significantly, this has resulted in the increment of CH4 formation rate, consistent with the increased carbon gasification and methanation. Carbon deposition was almost non-existent, particularly at 1023 K. In addition, the inclusion of hydrogen also has contributed to the decrease of CO2 and increase of CO formation rates. This was attributed to the reverse water-gas-shift reaction. Overall, both the CO2:CO and CO2:CH4 ratios decrease with the hydrogen partial pressure.